When Gender Kicks In: An Experimental Study of Work from Home and Attitudes to Household Work and Childcare - Andreas Kotsadam; Mette Løvgren; Nicolas Moreau; Elena G. F. Stancanelli; Arthur van Soest (Institute of Labor Economics (IZA), 2025)
We study how working from home links to gendered attitudes about household work and childcare. Using a vignette experiment embedded in a regular Dutch population representative survey, we randomly vary the gender of the partner working from home in a hypothetical dual-earner couple. When presented with various routine and emergency chores, respondents, on average, agree that the partner working from home should execute them. These effects are significantly larger when the vignette randomly depicts a man, rather than a woman, working from home, but these gender differences in respondents' expectations vanish in a scenario where no partner works from home. All in all, the evidence gathered indicates that Work from Home may blast rather than boost gender norms around household work and childcare.
Keywords: D13; D83; J16; J22; M54; 330; work from home; household work; gender norms; vignette